IDENTIFICATION OF ETHNIC ACTORS: THE VARIATION OF THE BIOGRAPHIC MODELS AND POSSIBILITIES - Монолатій, І. С. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
Тhe features of the research biography of ethno-political dimension are considered. Based on the achievements of political science, history and regional studies substantiated the thesis that current models biohrafiky to isolate ten models of the biography of the hero biographical study: mosaic, biographical, museum, estimates, tourist, “biographical rebellion”, detective, psychological, “speaker dead” and scientific.